Lectoescritura y su incidencia en los procesos de aprendizaje de los estudiantes del segundo año de educación básica - Morales Sánchez, Yessica Alexandra (2018)
As the child learns the letters and their groups, he learns to read, the printed words are gradually invested with different linguistic properties that can be more or less striking, depending on the stage of the reading development in which he is the child, these properties are derived from the linguistic codes that are the abstract mental representations of the different subsystems of language: phonological codes, semantic codes and syntactic / grammatical codes. In the present research work is intended to show the incidence of literacy in the teaching-learning processes of students in the second year of basic education, for which the types of descriptive and exploratory research was applied, with the help of inductive and deductive methods , data collection techniques such as observation, survey and interview aimed at parents and teachers of the institution, indicating that only sometimes strategies are applied to improve reading and the learning process is limited. of the students, for which purpose it is proposed to carry out a didactic guide of innovative strategies and techniques for the development of reading and writing skills and to improve the teaching-learning process.